THE POWER OF GAMES TO LEARN MATHEMATICS: AN OVERVIEW - Ariyadi Wijaya (PYTHAGORAS Jurnal Pendidikan Matematika, 2009)
The central principle of Realistic Mathematics Education is that the learning of mathematics needs to be laid on meaningful situation; either meaningful problems or activities. Many researches found that activities of game playing are meaningful to students and can be effective tools for enhancing learning and understanding of complex subject matter. Consequently, this article focuses on the benefit of games to support the learning of mathematics and the role of teacher in conducting game-based learning.Keywords : Realistic Mathematics Education, game-based learning, the role of teacher